Development of Augmented Reality (AR)-Based Learning Media for Facial Skin Care Subject - Gholiya Ghiska Putri Zuda; Putu Sudira (Journal of Educational Sciences, 2026)
This study was conducted to address the need innovative learning media that can effectively visualize facial skin care materials and improve students’ learning motivation. Conventional learning media are considered less optimal for presenting practical and visual content, therefore Augmented Reality (AR) was developed as an alternative learning medium. This study aimed to examine the ability of AR to visualize facial skin care materials, increase learning motivation, evaluate its effectiveness, analyze student learning outcomes before and after implementation, and identify media that meet student needs. This research used a research and development approach with the Multimedia Development Life Cycle (MDLC) model. The subjects were 35 eleventh-grade Beauty Care students of SMK Negeri 6 Semarang in the 2025/2026 academic year, selected using total sampling. Data were collected through questionnaires, pretests and posttests, and documentation, and analyzed descriptively. The results showed that AR learning media were interactive, real-time, flexible, and attractive. Expert validation resulted in an average score of 86.48% (Very Good). Student learning outcomes increased from 63.28 (pretest) to 91.08 (posttest), with an N-Gain value of 0.86 (high). Student responses reached 84.85% in the positive category. These findings indicate that AR-based learning media are effective and feasible for facial skin care learning.